INVESTIGATION OF THE EFFECT OF SOCIAL MEDIA MARKETING ON DOCTOR BRANDING IN THE HEALTH SECTOR - Fatma Nuray Kuşcu; Yunus Emre Öztürk; Ali Göde (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In this research, it was conducted to examine the effect of social media marketing on doctor branding. In line with the purpose of the research; 547 people selected by simple random sampling method among the students continuing their education at the university constitute the research sample group and the data were collected by applying a face-to-face questionnaire. In the research, "Personal Information Form", "Social Media Marketing Scale in the Health Sector" and "Doctor Branding Scale" were used. Data were analyzed with SPSS. As a result of determining that the data are normally distributed as a method of analysis; simple linear regression, pearson correlation, ANOVA and independent groups t test were applied. As a result of the research, it was determined that the social media marketing of the participants had a statistically significant and positive effect on doctor branding. In the light of these results, it is predicted that the level of doctor branding will increase as individuals increase social media marketing in the health sector.